AUGMENTED REALITY KATALOG PENJUALAN PERANGKAT KERAS MENGGUNAKAN MAGIC BOOK BERBASIS ANDROID - Septian Aderay Olii; Tajuddin Abdillah; Rahman Takdir (Diffusion: Journal of Systems and Information Technology, 2021)
Abstract At this time almost all circles have used information technology and technology itself is not something that is foreign to society in general. With the development of technology today, it will be easier for users to fulfill their needs and digital product marketing catalogs. The purpose of this research is to design and implement an augmented reality application of hardware sales catalogs using an android-based magic book. The author uses the Multimedia Development Life Cycle method. The purpose of this study is to design and implement an augmented reality application of hardware sales catalogs using an android-based magic book. The use of magic books to display 3D animated models by reading the marker symbols using the camera. Keywords : Android; Augmented Reality; Marker-based Tracking; Multimedia Developmennt Life Cycle; Unity; Vuforia